Uncharged Selenium Rings as Terminal and Bridging Ligands in Selenium‐Rich Iridium Clusters1. Issue 8 (2nd May 2014) - Stolze, Karoline; Ruck, Michael
Abstract Purple air‐stable crystals of Ir8Se40Br10 were obtained by reacting Ir in an excess of Se and SeBr4 at 300 °C for two weeks. The monoclinic crystal structure [space group P21/c, a = 1371.9(1) pm, b = 1108.1(1) pm, c = 2058.2(1) pm, β = 106.897(2)° at 296(1) K] consists of uncharged clusters Ir8Se40Br10 = (Ir3+)8(Se22–)(Se42–)6(Se7)2(Br–)10. The iridium(III) cations are coordinated octahedrally by selenium and bromide ions. While the oligoselenide anions provide high intra‐cluster connectivity, μ6‐η2 in the case of Se22– and μ4‐η3 for Se42–, the terminal uncharged Se7 rings have boat conformation and are η1‐coordinating. About 10 % of the Se7 rings are substituted by Se6 rings with chair conformation. A similar reaction using SeCl4 yielded vermillion air‐stable crystals of Ir2Se9Cl6. X‐ray diffraction on a single‐crystal revealed a tetragonal lattice (space group I41/a) with a = 1229.8(1) pm and c = 2365.5(2) pm at 296(1) K. In the Se9(IrCl3)2 cluster, a crown‐shaped uncharged Se9 ring coordinates two iridium(III) cations as a bridging bis‐tridentate ligand. Three terminal chloride ions complete the distorted octahedral coordination of each transition metal atom.